CHANGES OF MORPHOLOGY AND IMMUNOREACTIONS IN THE VESSELS OF KIDNEYS, HEART AND AORTA IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Jakovtsova, I.I.; Topchij, I.I.; Daniluk, S.V.; Kirienkow, A.N.; DunaievskaМ.М. (Ukrainian Journal of Nephrology and Dialysis, 2016)
Chronic kidney diseases are etiology of complications in cardiovascular system. Structural and functional changes ofendothelium on a background ofimmunoreactions lies in basis ofthese disorders and complications. The aim of research was to study of morphologicalfeatures of kidneys and immune reactions in the vessels of kidneys, heart, aorta inpatients with CDK. Materials and methods. An autopsy material of the 20 dead’s age from 45 to 55 was investigated . The deceased had signs ofchronic desease of kidneys (CDK). Theprimary monoclonal antibody (PMA) company ofDAKO (Denmark) Rady - to - Use were used to reveal of features of cellular immunoreactions in the zones of inflammatoryprocess. We used microscope Primo Star (Carl Zeiss) with theprogram AxioCam (ERc 5s). Results and discussion. Changes of kidneys vessels, coronary arteries and aorta were characterized of transformation similar with immune inflammation. Condition of endothelium was characterized disorder of endothelization and manifest irregularity, lumpiness with outcrop of wide intercellular connections. All this proses bring to activation of apoptosis. Conclusion. Disturbance of vessel morphology and activity of immunoinflammatory reaction can be one of main cause ofdeveloping cardio-vascular complication.